VD_FINDINFO Jug / 2023 / 1 vom 16. Mai 2022 - VD Tribunal cantonal (2022)
VIOL, REJET DE LA DEMANDE, EXPULSIONDROIT PÉNAL | 106 CP, 190 CP, 40 CP, 46 al. 1 CP, 47 CP, 49 al. 1 CP, 51 CP, 66a al. 1 let. h CP, 91 al. 1 LCR, 19a ch. 1 LStup